The Effect of Oxytocin Massage on Discharge Breast Milk for Postpartum Mothers in Batam City - Desi Ernita Amru; Dede Maysarah; Nurul Huda (International Journal of Public Health Excellence (IJPHE), 2023)
Breast milk (ASI) is the first and best food that must be given to babies because it contains nutrients that are needed in the process of growth and development of children's intelligence. Increasing breast milk production can be done in two ways, namely pharmacologically and non-pharmacologically. One action that can be done to help the release of breast milk is through oxytocin massage which can be done by massaging the area around the back (pars thoratica vertebrae) to stimulate the release of milk. The purpose of this study is to determine the effect of oxytocin footing on breast milk expenditure in postpartum mothers in Batam City in 2023. The type of research used is quasi-experiment with pretest research design and posttest one group design. The data analysis used was Paired t-test and this study was conducted for 5 days. The sampling technique in this study was purposive sampling with 17 respondents. The results of this study based on statistical tests obtained P value = 0.0001 with a difference of 3.06%, which means that it can be a significant difference before and after soy milk consumption. Conclusion: there is a significant influence between oxytocin footing on breast milk production in postpartum mothers in the working area of Batu Aji Health Center Batam City. Researchers hope that postpartum mothers can do oxytocin steps to increase milk production